2018
DOI: 10.14195/2182-7974_31_1_7
|View full text |Cite
|
Sign up to set email alerts
|

[Recensão a] Thomas, D., Fowler, S., & Johnson, V. (2017) - The Silence of the Archive.

Abstract: https://doi.org/10.14195/2182-7974_31_1_7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…In this case, the ability of the variant to inhibit poly-ADP ribosylation by PARP1 would likely be affected by the stoichiometry of present macro domains, as well as their species. 23,25,51 Luger and Chakravarthy also observed that macroH2A and hybrid constructs, to a lesser extent, were resistant to exchange of dimers with the nucleosome assembly protein 1 (NAP1). In isolation of this information, our energetic analysis would suggest that the hybrid NCP should be the most resistant to this exchange, as the complex is the most stable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the ability of the variant to inhibit poly-ADP ribosylation by PARP1 would likely be affected by the stoichiometry of present macro domains, as well as their species. 23,25,51 Luger and Chakravarthy also observed that macroH2A and hybrid constructs, to a lesser extent, were resistant to exchange of dimers with the nucleosome assembly protein 1 (NAP1). In isolation of this information, our energetic analysis would suggest that the hybrid NCP should be the most resistant to this exchange, as the complex is the most stable.…”
Section: Discussionmentioning
confidence: 99%
“…13 Because of its involvement in transcriptional repression, macroH2A enrichment and depletion have been linked to regulation of pluripotent and cancerous cells. 25,26 While the effects of macroH2A substitution continue to be studied, there has been very little focus on the necessary quantities of macroH2A required to invoke each of these observed mechanisms. That is to say, do both dimers need to be substituted with macroH2A, or is the replacement of a single dimer sufficient?…”
Section: Introductionmentioning
confidence: 99%